The Level of Psychological Happiness of School Principals in the Al-Qardah Al-Shati Municipality (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
The aim of this research is to determine the level of psychological happiness of school principals in the municipality of Al-Qarda Al-Shati.The study sample was (32) school principals, and the researcher used the psychological happiness scale, the Califonia scale. The research reached the following results:There are no statistically significant differences in the level of availability of the degree of psychological happiness for school principals according to the academic degree variable in the municipality of Al-Qarda Al-Shati. There are no statistically significant differences in the level of availability of the degree of psychological happiness for school principals according to the variable of years of service, and there are no statistically significant differences in the availability of happiness. Psychological analysis of school principals according to the gender variable.
Keywords: Psychological happiness; school principals